Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A revised Proterozoic tectono-stratigraphy of the South Nicholson region, Northern Territory, Australia—insights from SHRIMP U–Pb detrital zircon geochronology - C. J. Carson; N. Kositcin; J. R. Anderson; P. A. Henson (Australian Journal of Earth Sciences, 2026)

Shale brittleness within the Paleoproterozoic Isa Superbasin succession in the South Nicholson region, Northern Australia - A. H. E. Bailey; A. J. M. Jarrett; L. Wang; B. L. Reno; E. Tenthorey; C. Carson; P. Henson (Australian Journal of Earth Sciences, 2026)

Inter-method differences (SIMS vs. IRMS) in oxygen isotope fractionation: insights from Chinook salmon otoliths - Kohma Arai; Malte Willmes; George E. Whitman; Kenneth W. Zillig; Cassidy J. Cooper; Nozomi Matsuda; Elizabeth A. Bell; Kevin D. McKeegan; Levi S. Lewis; Carson A. Jeffres; Rachel C. Johnson (Geochimica et Cosmochimica Acta, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Evaluation of SARS-CoV-2 antibody detection methods for wild Cervidae - Joshua Hewitt; Grete Wilson-Henjum; Jeffrey C. Chandler; Aaron T. Phillips; Diego G. Diel; W. David Walter; Alec Baker; Jennifer Høy-Petersen; Guillaume Bastille-Rousseau; Tadao Kishimoto; George Wittemyer; Jeremy Alder; et al. (Preventive Veterinary Medicine, 2025)

Functional brain network correlates of cardiorespiratory fitness and moderation by depression symptoms - Lauren R. Borrell; Andrew C. Venezia; J. Carson Smith (Brain Structure and Function, 2025)
Cardiorespiratory fitness may protect against or alleviate depression through neuroplastic mechanisms within disrupted brain networks underlying cognitive and affective symptoms. There is a scarcity of research examining the effects of cardiorespiratory fitness on functional brain networks in representative samples spanning adulthood. Further, little is known about the interaction of cardiorespiratory fitness with depression in these networks. To address this problem, this study made use of the NKI-Rockland sample dataset and magnetic resonance imaging to examine whether functional brain network features associated with cardiorespiratory fitness were moderated by depression symptom severity in a community sample of 217 participants (134 females, 83 males) between the ages of 18 and 71 ( M = 43.8 years, SD = 16.2). Cardiorespiratory fitness was positively associated with whole-brain modularity, between-network connectivity of the central executive and salience networks, and within-network connectivity of the default mode, central executive, and salience networks. The association of cardiorespiratory fitness and default mode network connectivity was stronger in the presence of moderate-to-severe depression symptoms. Taken together, these observations lend support to prior work that has demonstrated the associations of cardiorespiratory fitness with reduced concurrent and prospective depression risk and symptom severity. Depression symptoms moderated default mode network connectivity, suggesting that cardiorespiratory fitness may differentially impact neural substrates for those with moderate-to-severe depression symptoms.

Genomics and serotyping of Tenacibaculum maritimum outbreak isolates from Australia and New Zealand for guided vaccine development and stewardship - O. Rudenko; C. Angelucci; K. Kumanan; L. Delisle; J. Carson; R.N. Morrison; K.S. Hutson; A.C. Barnes (Aquaculture, 2025)

A global survey for dust devil vortices on mars using MRO context camera images enabled by neural networks - Susan J. Conway; Valentin T. Bickel; Lori K. Fenton; Manish R. Patel; Helen C. Carson; Antoine Blouin; Justin Crevier; Evan Blanc; Bao Nhi Nguyen; James A. Holmes; Brian Jackson; Lonneke Roelofs (Planetary and Space Science, 2025)

Springtime upwelling conditions influence microbial communities and dissolved thiamin compounds in the California Current Ecosystem - Kelly C. Shannon; Gillian St. John; Robin Gould; Christopher Hartzell; Hailey Matthews; Elizabeth J. Brennan; Luis M. Bolaños; Steven T. Lindley; John C. Field; Nate Mantua; Rachel Johnson; Carson Jeffres; et al. (Limnology and Oceanography, 2025)
Understanding dissolved concentrations of the essential coenzyme thiamin (vitamin B 1 ) can provide insights into the biological controls on highly productive upwelling systems such as the California Current Ecosystem. To connect thiamin availability with microbial communities in the California Current Ecosystem, we measured concentrations of dissolved thiamin and its biochemically related moieties (thiamin congeners) and 16S rRNA gene‐based microbial communities during the spring. We found that strong upwelling caused a depletion of dissolved thiamin precursor compounds and abiotic degradation products relative to periods of weak upwelling. Specific microbial taxa, including species of SAR11 ecotypes, Candidatus Nitrosopumilus, and SUP05 cluster, were also significantly enriched with strong upwelling. Our data provide evidence that alterations to microbial communities in the mixed layer that occur as a result of upwelling could constrain the availability of dissolved thiamin and its chemical congeners in the California Current Ecosystem.

Dynamics of hydrogen–ammonia–natural gas lean-premixed high-pressure flames - Tristan T. Shahin; Alexander J. Hodge; Benjamin K. Murdock; Thomas N. McLean; Keaton C. Koenig; Rohan M. Gejji; Robert P. Lucht; Carson D. Slabaugh (Fuel, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Native tree species prosper while exotics falter during gap-phase regeneration, but only where deer densities are near historical levels - Anthony C. Yacucci; Walter P. Carson; Jenna C. Martineau; Curtis D. Burns; Brian P. Riley; Alejandro A. Royo; Thomas P. Diggins; Ian J. Renne (New Forests, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Acardius acephalus in an aborted lamb - A. Morey Matamalas; F. Ridout; J. Dubuc; C. Bianco; R. Reichel; A. Carson (Journal of Comparative Pathology, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Temporal emergence of age-associated changes in cognitive and physical function in vervets (Chlorocebus aethiops sabaeus) - Brett M. Frye; Payton M. Valure; Suzanne Craft; Mark G. Baxter; Christie Scott; Shanna Wise-Walden; David W. Bissinger; Hannah M. Register; Carson Copeland; Matthew J. Jorgensen; Jamie N. Justice; Stephen B. Kritchevsky; et al. (GeroScience, 2021)

Sex differences in changes of protein synthesis with rapamycin treatment are minimized when metformin is added to rapamycin - Christopher A. Wolff; Marcus M. Lawrence; Hunter Porter; Qian Zhang; Justin J. Reid; Jaime L. Laurin; Robert V. Musci; Melissa A. Linden; Frederick F. Peelor; Jonathan D. Wren; Joseph S. Creery; Kyle J. Cutler; et al. (GeroScience, 2021)

The microbiota influences the Drosophila melanogaster life history strategy - Amber W. Walters; Rachel C. Hughes; Tanner B. Call; Carson J. Walker; Hailey Wilcox; Samara C. Petersen; Seth M. Rudman; Peter D. Newell; Angela E. Douglas; Paul S. Schmidt; John M. Chaston (Molecular Ecology, 2020)
Organisms are locally adapted when members of a population have a fitness advantage in one location relative to conspecifics in other geographies. For example, across latitudinal gradients, some organisms may trade off between traits that maximize fitness components in one, but not both, of somatic maintenance or reproductive output. Latitudinal gradients in life history strategies are traditionally attributed to environmental selection on an animal's genotype, without any consideration of the possible impact of associated microorganisms (“microbiota”) on life history traits. Here, we show in Drosophila melanogaster , a key model for studying local adaptation and life history strategy, that excluding the microbiota from definitions of local adaptation is a major shortfall. First, we reveal that an isogenic fly line reared with different bacteria varies the investment in early reproduction versus somatic maintenance. Next, we show that in wild fruit flies, the abundance of these same bacteria was correlated with the latitude and life history strategy of the flies, suggesting geographic specificity of the microbiota composition. Variation in microbiota composition of locally adapted D. melanogaster could be attributed to both the wild environment and host genetic selection. Finally, by eliminating or manipulating the microbiota of fly lines collected across a latitudinal gradient, we reveal that host genotype contributes to latitude‐specific life history traits independent of the microbiota and that variation in the microbiota can suppress or reverse the differences between locally adapted fly lines. Together, these findings establish the microbiota composition of a model animal as an essential consideration in local adaptation.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Erratum to: Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Andrew Leis; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Preliminary characterization of Tasmanian aquareovirus (TSRV) isolates - Sandra C. Zainathan; Jeremy Carson; Mark St. J. Crane; Lynette M. Williams; John Hoad; Nicholas J. G. Moody; Nicholas Gudkovs; Sandra Crameri; Alex D. Hyatt; John Young; Barbara F. Nowak (Archives of Virology, 2017)

Ranavirus could facilitate local extinction of rare amphibian species - Julia E. Earl; Jordan C. Chaney; William B. Sutton; Carson E. Lillard; Andrew J. Kouba; Cecilia Langhorne; Jessi Krebs; Rebecca P. Wilkes; Rachel D. Hill; Debra L. Miller; Matthew J. Gray (Oecologia, 2016)

Coastal sea level changes, observed and projected during the 20th and 21st century - M. Carson; A. Köhl; D. Stammer; A. B. A. Slangen; C. A. Katsman; R. S. W. van de Wal; J. Church; N. White (Climatic Change, 2016)

Development and application of molecular methods ( PCR ) for detection of Tasmanian Atlantic salmon reovirus - S C Zainathan; G Carlile; J Carson; K A McColl; M St. J Crane; L M Williams; J Hoad; N J G Moody; H M Aiken; G F Browning; B F Nowak (Journal of Fish Diseases, 2015)
Molecular ( PCR ) diagnostic tests for the detection and identification of aquareovirus in general, and Tasmanian Atlantic salmon reovirus ( TSRV ) specifically, were developed, and their diagnostic sensitivity and specificity were determined and compared with virus isolation in cell culture. Intralaboratory and interlaboratory comparison of PCR (conventional hemi‐nested RT‐PCR & RT ‐ qPCR ) and virus isolation in cell culture using finfish cell lines, CHSE ‐214 and EPC , was carried out for the detection and identification of TSRV using field samples of farmed Atlantic salmon Salmo salar, L. from various aquaculture sites around Tasmania. The interlaboratory comparison of diagnostic methods was carried out between two laboratories, AAHL ‐ CSIRO and DPIPWE ‐Tasmania. A total of 144 fish from nine sites (12–33 fish per site) were sampled from two regions of Tasmania (Tamar River estuary in the north and Huon River estuary in the south‐east) during late spring to early summer of 2009, and the data were analysed using different statistical approaches. The prevalence of TSRV ranged from 6% to 22% in both regions. All the diagnostic methods (data from both laboratories) had high specificity, while the estimated sensitivity varied between tests with RT ‐ qPCR being the most sensitive (95.2%) method followed by virus isolation and then conventional hemi‐nested RT‐PCR .

Combination paracetamol and ibuprofen for pain relief after oral surgery: a dose ranging study - Hartley C. Atkinson; John Currie; John Moodie; Simon Carson; Steven Evans; James P. Worthington; Leon J. Steenberg; Eileen Bisley; Chris Frampton (European Journal of Clinical Pharmacology, 2015)

Conditions for the validity of SNP-based heritability estimation - James J. Lee; Carson C. Chow (Human Genetics, 2014)

Ecosystem classifications based on summer and winter conditions - Margaret E. Andrew; Trisalyn A. Nelson; Michael A. Wulder; George W. Hobart; Nicholas C. Coops; Carson J. Q. Farmer (Environmental Monitoring and Assessment, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Laboratory evaluation of sample collection methods (organs vs swabs) for T asmanian salmon reovirus detection in farmed A tlantic salmon, S almo salar L . - S C Zainathan; J Carson; M St J Crane; B F Nowak (Journal of Fish Diseases, 2013)
The use of swabs relative to organs as a sample collection method for the detection of Tasmanian salmon reovirus ( TSRV ) in farmed T asmanian A tlantic salmon, S almo salar L., was evaluated by RT ‐q PCR . Evaluation of individual and pooled sample collection (organs vs swabs) was carried out to determine the sensitivity of the collection methods and the effect of pooling of samples for the detection of TSRV . Detection of TSRV in individual samples was as sensitive when organs were sampled compared to swabs, and in pooled samples, organs demonstrated a sensitivity of one 10‐fold dilution higher than sampling of pooled swabs. Storage of swabs at 4 °C for t = 24 h demonstrated results similar to those at t = 0. Advantages of using swabs as a preferred sample collection method for the detection of TSRV compared to organ samples are evident from these experimental trials.

The Victoria and Birrindudu Basins, Victoria River region, Northern Territory, Australia: a SHRIMP U–Pb detrital zircon and Sm–Nd study - C. J. Carson (Australian Journal of Earth Sciences, 2013)

Determination of the compositional change (1999–2006) in the pine forests of British Columbia due to mountain pine beetle infestation - Colin Robertson; Carson J. Q. Farmer; Trisalyn A. Nelson; Ian K. Mackenzie; Michael A. Wulder; Joanne C. White (Environmental Monitoring and Assessment, 2009)

NeuroAIDS, Drug Abuse, and Inflammation: Building Collaborative Research Activities - Joan W. Berman; Monica J. Carson; Linda Chang; Brian M. Cox; Howard S. Fox; R. Gilberto Gonzalez; Glen R. Hanson; Kurt F. Hauser; Wen-Zhe Ho; Jau-Shyong Hong; Eugene O. Major; William F. Maragos; et al. (Journal of Neuroimmune Pharmacology, 2006)

Effects of paroxetine on cardiovascular response to mental stress in subjects with a history of coronary artery disease and no psychiatric diagnoses - Michael Golding; Michael Kotlyar; Stanley W. Carson; Sherri Hoyler; Cindy Lazarus; Colin Davidson; Joseph Guzzo; Eric Sontz; J. C. Garbutt (Psychopharmacology, 2005)

QTL associations for density and diameter in Pinus radiata and the potential for marker-aided selection - M. E. Devey; S. D. Carson; M. F. Nolan; A. C. Matheson; C. Te Riini; J. Hohepa (Theoretical and Applied Genetics, 2004)

Coral‐reef sounds enable nocturnal navigation by some reef‐fish larvae in some places and at some times - J. M. Leis; B. M. Carson‐Ewart; A. C. Hay; D. H. Cato (Journal of Fish Biology, 2003)
At Lizard Island, Great Barrier Reef, catches of fish larvae by light traps that broadcast nocturnal reef sounds (noisy traps) were compared with catches by quiet traps over two 2·5 week new‐moon periods in November (XI) 2000 and January (I) 2001. Three areas were sampled: near‐reef (NR, 500 m from the shore) in I, middle (M, 650 m) in I and XI and offshore (O, >1000 m) in XI. The most abundant taxa captured were Apogonidae, Blenniidae, Chaetodontidae, Lethrinidae, Mullidae and Pomacentridae. Significant differences in catch were found between areas, and a position effect was found at the O and M areas. At the NR and M areas, no taxa had significantly greater catches in quiet traps, but larvae of five taxa had significantly greater catches in noisy traps. These were (areas and times of greater catches): Apogonidae (NR; M XI), Mullidae (M I & XI), Pomacentridae (NR; M I & XI), Serranidae (M I) and Sphyraenidae (NR). At the offshore area, five taxa (Apogonidae, Blenniidae, Chaetodontidae, Mullidae and Pomacentridae) had significantly greater catches in quiet traps and only Lethrinidae had significantly greater catches in noisy traps. Thus some taxa (particularly apogonids and pomacentrids which had catches up to 155% greater in noisy traps, but also lethrinids and mullids, and perhaps others), were attracted to reef sounds at night, but this apparently varied with location and time. The sound‐enhanced catches imply a radius of attraction of the sound 1·02–1·6 times that of the light. More than 65 m from the speaker,the broadcast sound levels at frequencies typical of fish hearing were equivalent to background levels, providing a maximum radius of sound attraction in this experiment.

Role of peripheral afference during acquisition of a complex coordination task - R. G. Carson; C. J. Smethurst; M. Forner; D. P. Meichenbaum; D. C. Mackey (Experimental Brain Research, 2002)

Alleviation of aluminum toxicity to Rhizobium leguminosarum bv. viciae by the hydroxamate siderophore vicibactin - Nicola J. Rogers; Kerry C. Carson; Andrew R. Glenn; Michael J. Dilworth; Martin N. Hughes; Robert K. Poole (BioMetals, 2001)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Nocardiosis in tank‐reared Atlantic salmon, Salmo salar L. - M P. Bransden; J. Carson; B L. Munday; J H. Handlinger; C G. Carter; B F. Nowak (Journal of Fish Diseases, 2000)
Nocardiosis is an infection caused by aerobic Gram‐positive, branching, filamentous rods of the genus Nocardia . The organism is resident in both soil and plants ( Austin & Austin 1993 ; Frerichs 1993 ), and is closely related to Mycobacterium spp. Nocardiosis caused by Nocardia asteroides and N. seriolae (previously N. kampachi ) has been reported in several finfish species, both freshwater and marine. The first reported incidence was recorded by Valdez & Conroy (1963) in neon tetras, Hyphessobrycon innesi (Myers), and subsequently in other fish species, some of commercial significance including rainbow trout, Oncorhynchus mykiss (Walbaum) ( Snieszko, Bullock, Dunbar & Pettijohn 1964 ), brook trout, Salvelinus fontinalis (Mitchill), ( Campbell & MacKelvie 1968 ) and yellowtail, Seriola quinqueradiata (Temminck & Schlegel; Kubota, Kariya, Nakamura & Kira 1968 ). Despite two of these incidences occurring in salmonids, infection by Nocardia spp. in Atlantic salmon, Salmo salar L., has not previously been reported.

Evidence for polynuclear iron(III) clusters in the root nodule bacterium, Rhizobium leguminosarum bv. viciae WSM710 - Timothy G. St. Pierre; Kerry C. Carson; John Webb; Andrew R. Glenn; Michael J. Dilworth (BioMetals, 1999)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Specificity of siderophore-mediated transport of iron in rhizobia - K. C. Carson; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1994)

Siderophore and organic acid production in root nodule bacteria - K. C. Carson; S. Holliday; A. R. Glenn; M. J. Dilworth (Archives of Microbiology, 1992)